PENGARUH TRANSFER PRICING, KOMISARIS INDEPENDEN, PROFITABILITAS, DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTOR CONSUMER GOODS TAHUN 2020-2024 - Sophia, Ananda; Sartika, Novira (Penerbit Lafadz Jaya, 2025)
Tax avoidance has become a common strategy among consumer goods companies in Indonesia to reduce tax burdens legally. This study aims to examine the effects of transfer pricing, independent commissioners, profitability, and leverage on tax avoidance in consumer goods companies listed on the Indonesia Stock Exchange from 2020 to 2024. Employing a quantitative explanatory research design, secondary data from 78 observations of 16 purposively sampled firms were analyzed. Data were processed using SPSS 29 with multiple linear regression and classical assumption tests. The results indicate that simultaneously, the variables significantly influence tax avoidance. However, only profitability has a significant partial effect, where higher profitability encourages greater tax avoidance. Transfer pricing, independent commissioners, and leverage showed no significant partial effects, suggesting that internal governance and debt structure are not dominant factors individually. The study concludes that profitability management is the primary driver of tax avoidance in this sector, while regulatory and governance mechanisms need strengthening. These findings provide insights for policy-makers to enhance tax compliance and corporate governance.